Measurements of Positively Charged Ions in Premixed Methane-Oxygen Atmospheric Flames. Issue 4 (3rd April 2017) - Alquaity, Awad B. S.; Han, Jie; Chahine, May; Selim, Hatem; Belhi, Memdouh; Sarathy, S. Mani; Bisetti, Fabrizio; Farooq, Aamir
ABSTRACT: Cations and anions are formed as a result of chemi-ionization processes in combustion systems. Electric fields can be applied to reduce emissions and improve combustion efficiency by active control of the combustion process. Detailed flame ion chemistry models are needed to understand and predict the effect of external electric fields on combustion plasmas. In this work, a molecular beam mass spectrometer (MBMS) is utilized to measure ion concentration profiles in premixed methane–oxygen argon burner-stabilized atmospheric flames. Lean and stoichiometric flames are considered to assess the dependence of ion chemistry on flame stoichiometry. Relative ion concentration profiles are compared with numerical simulations using various temperature profiles, and good qualitative agreement was observed for the stoichiometric flame. However, for the lean flame, numerical simulations misrepresent the spatial distribution of selected ions greatly. Three modifications are suggested to enhance the ion mechanism and improve the agreement between experiments and simulations. The first two modifications comprise the addition of anion detachment reactions to increase anion recombination at low temperatures. The third modification involves restoring a detachment reaction to its original irreversible form. To our knowledge, this work presents the first detailed measurements of cations and flame temperature in canonical methane–oxygen-argon atmospheric flat flames. The positive ion profiles reported here may be useful to validate and improve ion chemistry models for methane-oxygen flames.